Effect of Ethylene Glycol Concentration on Membrane Permeability of One- and Two Cell Murine Embryos - Pishko, O. V. (Problems of Cryobiology and Cryomedicine, 2004)
The permeability coefficients for one- and two-cell embryos for ethylene glycol (EG) and water molecules using the volumetry method and physical-chemical model, describing the mass exchange processes between a cell and its environment, were determined. The cleavage was shown as not affecting the transport characteristics of membranes, but augmenting their resistance to the increased cryoprotectant concentration effect.